Influence of Inclusion Policies on Women’s Parliamentary Representation in Nepal - Adhikari, Bhawani Shankar (Creative Vision: Multidisciplinary Journal of PMC, 2025)
This research aims to examine the status of women’s involvement in the Nepalese Parliament, particularly before and after the implementation of inclusion policies as the legal provision has been made through the constitutions of Nepal. It has covered the historical context, policy framework, and statistical data concerning female participation in parliament. The issue of women’s political engagement in Nepal has gained prominence following the significant revolution in 2006. Statistical evidence has indicated a marked positive impact from the introduction of quota systems, which have been found as a part of broader inclusive policies aimed at increasing female representation in Nepal’s parliament. Through document analysis and observation of electoral outcomes, the presence of women in the House of Representatives has been found to be notably increased. However, relying solely on quota systems cannot be sufficed to achieve gender equality in the inclusiveness and participation of the women in the parliamentary system in Nepal. The inclusion policy must continue to evolve, taking more effective measures to further enhance women’s inclusivity and pave the way towards a gender-equitable society. The ways of improving the condition of the women’s inclusion in the parliamentary system in Nepal have been identified as the traditional gender roles, political culture, educational barriers, legal and institutional constraints, cultural and social norms, violence, party politics, legal reforms and enforcement, capacity building, addressing cultural and social norms, support services, and the educational awareness to be improved for the active participation and inclusion of women in the parliamentary system in Nepal.